Die geographischen Typen der Brache in Ungarn - Berényi, István (ERDKUNDE, 1980)
The area of arable land diminished by 7.8% between 1945-1961, which meant an annual reduction of 30 thousand hectares. This reduction became more moderate (11 thousand hectares) 1963-1972; nevertheless, the area left unploughed was growing. For the exploration of the causes of the growing and territorial expansion of unploughed land the investigation of Borsod-Abauj-Zemplen county seemed to be the most suitable area because the ecological endowments and the regional development in the socio-economic development of this administration unit can reflect well the peculiarities of the whole country. 3 regional types of unploughed land have been demarcated in the county of investigation: the border region, the Borsod industrial region and the alluvium of the Tisza river. A regional connection could be stated between the appearance of unploughed land and the following factors: a) Two main tendencies can be observed in the transformation of land utilization between 1935-1970 (Fig. 3): the growth of the built-up area and the reduction of agricultural land. The share of unploughed land is high in regions of rapid and large-scale transformation of the land use structure (border regions and urban-industrial agglomerations). b) A relation can be found between the value number (fertility) of soil and the share of ploughed land (Tisza valley). c)There is also a regional connection between the reduction of agricultural population and the expansion of ploughed land, although, it is not unambiguous. For example, at the edge of the Great Plain (the Southern part of the county) there was a strong reduction of the agrarian population. Nevertheless, the area of unploughed land has not grown because large farms have consolidated the land) A definite connection can be found between the production level of farms and the appearance of unploughed land (Fig. 5). The appearance of unploughed land has been summarized in a spatial structural model; ploughland appears, first of all, at the border of urban-industrial agglomerations and agricultural areas and of agricultural areas and natural ones, where the functional change of the area is the strongest.